2011
DOI: 10.3892/or.2011.1438
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator-stimulated phosphoprotein regulates osteosarcoma cell migration

Abstract: Abstract. Vasodilator-stimulated phosphoprotein (VASP) has been reported to play an important role in the process of cell migration and tumor metastasis. However, to date, no study has examined VASP expression and its function in osteocarcoma cells. In this study, we analyzed the effect of VASP on osteosarcoma cell migration and the signal transduction pathways involved. We used two osteosarcoma cell strains (Mg-63 and Saos-2 cells) with different metastatic potential. Silencing of VASP gene expression was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The intensity of Mena expression increases from premalignant to malignant lesions in various organs, including the large bowel, stomach, cervix and salivary glands ( 8 , 32 ). Aggressive and migratory Mg-63 osteosarcoma cells contain comparatively higher expression levels of VASP at the transcriptional and translational levels, compared with the less aggressive Saos-2 osteosarcoma cells ( 33 ). Overexpression of VASP in wild-type NIH 3T3 cells results in metaplasia to cancer cells ( 34 ), and the increased expression level of VASP in lung adenocarcinoma correlates with lower cellular differentiation and an increased pathological stage of the tumor ( 8 ).…”
Section: Discussionmentioning
confidence: 94%
“…The intensity of Mena expression increases from premalignant to malignant lesions in various organs, including the large bowel, stomach, cervix and salivary glands ( 8 , 32 ). Aggressive and migratory Mg-63 osteosarcoma cells contain comparatively higher expression levels of VASP at the transcriptional and translational levels, compared with the less aggressive Saos-2 osteosarcoma cells ( 33 ). Overexpression of VASP in wild-type NIH 3T3 cells results in metaplasia to cancer cells ( 34 ), and the increased expression level of VASP in lung adenocarcinoma correlates with lower cellular differentiation and an increased pathological stage of the tumor ( 8 ).…”
Section: Discussionmentioning
confidence: 94%
“…These results indicated that HCMV-induced endothelium hyperpermeability may be mediated by Rac1 and VASP-associated cell-cell junction remodeling. In addition, as VASP is a downstream effector of Rac1 in osteosarcoma cells, interference of Rac1 in the cells led to a significant reduction in VASP expression ( 21 ). Additionally, consistent with previous reports, the EC data from the current study also revealed that interfering with the expression of Rac1 using siRNA-Rac1 could inhibit the expression of VASP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rac1 regulates the alterations of endothelial permeability by mediating skeletal protein remodeling ( 20 ). It has been demonstrated that VASP is a downstream effector of Rac1 in osteosarcoma cells ( 21 ). Therefore, Rac1-mediated VASP activation may be involved in maintaining the barrier function of ECs.…”
Section: Introductionmentioning
confidence: 99%
“…Nayak et al [ 59 ] demonstrated that the level of phosphorylated VASP (Ser239) is upregulated by knocking down lysosome-associated membrane protein 3, thereby weakening the aggressiveness and metastasis of esophageal squamous cell carcinoma cells. Wu et al [ 60 ] suggested that Rac1 knockdown leads to VASP expression in osteosarcoma cells, attenuating their migration and metastasis. Li et al [ 61 ] showed that circRFX3 promoted glioma progression by regulating the miR-1179/miR-1229-VASP axis.…”
Section: Relationship Between Vasp and Malignant Tumorsmentioning
confidence: 99%